Nanocoolant alternative for cooling elements by UMP researchers - Kumaran, Kadirgama; Devarajan, Ramasamy (2020)
The cooling system is an essential element in our daily life. Even our body needs a cooling system to balance out the temperature among the organs. The automotive and manufacturing industries need a sound cooling system for the equipment and auxiliary devices. With the advancing technology in electric automotive, manufacturing, and high-speed cars, the cooling system has become a more critical element. Metalworking fluid is the standard cutting fluid that has been used widely in many sectors. According to Grand View Research (2018), the global metalworking fluid market in 2017 was valued at USD10.3 billion. Figure 2 shows the annual usage of metalworking fluid. The usage of metalworking fluid has been forecast to increase by 4.4% by the end of 2025. Figure 3 shows the metalworking fluid market size by sector, where machinery sector used about 43% of the total global metalworking fluid annually.